DAMPAK PERUBAHAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 KE UNDANG-UNDANG NOMOR 23 TAHUN 2014 TERHADAP PENGALIHAN KEWENANGAN MANAJEMEN PENDIDIKAN MENENGAH - Jesly Yuriaty; Martha Carolina (Pusat Kajian Anggaran, 2017)
This study aims to determine the government affairs concurrent in Act Nomor 23 year 2014 and its comparation with Act Nomor 32 year 2004 regarding The Authorities of Middle Education will be transferred From District To Province. This research used method of Qualitative Descriptive Research. The results showed The Authorities Transfer of Middle Education to Province will make impact in order to uniform middle education policy in Province, to lessen the work load in District and efficiency of region allocation budget (APBD). Yet, it can reduced the significance of autonomy that potentially disadvantageous the constitutional rights. Coordination amongst government needed thus mitigate the overlap in authorities/discrepancy between regions.